IMPROVING THE METHODOLOGY OF TEACHING LISTENING AND READING THROUGH AUTHENTIC MATERIALS IN RFL INSTRUCTION - Mavlyanova Nilufar Ibadillayevna (Modern American Journals, 2025)
The article examines modern approaches to teaching listening and reading in Russian as a Foreign Language (RFL) using authentic materials. It describes methodological stages for working with genuine texts, audio, and video materials and proposes interactive, creative techniques aimed at increasing students’ motivation and the effectiveness of language acquisition. Special attention is given to digital technologies, adapting materials to learners’ proficiency levels, and developing sociocultural competence. Examples of classroom tasks and procedures applicable in a university setting are provided.
Keywords: RFL, authentic materials, listening, reading, teaching methodology, digital technologies, motivation.